The folk song in its essence: an ethnomusicological analysis of five traditional Brazilian popular songs - Vaccari, Pedro Razzante [UNESP] (Univ Fed Rio De Janeiro, Fac Letras, 2022)
We looked for researching the origins and main sources of two popular traditional brazilian songs, that are: the Maracatu song Loanda and the indigenous song Natio, from Paresis natives. They represent a brazilian popular music stylistic panorama, as urban, rural or made by the natives themselves. They have, therefore, in addition to aesthetic-musical idiosyncrasies, characteristics specific to each region and ethnic group that produced them. They are a cultural source that reflect the enormous profusion of songs that the continental country had produced until the 1930s, when the Nationalist Movement broke out in Brazil, which sought to unify the languages of Literature, Music and Plastic Arts in favor of an artistic totality that unveiled the meanings of Nationality. The songs in question were brought together and harmonized by brazilian northwest composer Jose Siqueira 1907-1985), and released on disc in 1939. In them we can see portraits of different shades of national color: popular music with rural percussion, indigenous ritual and Afro brazilian religious music. They are pieces of a larger picture, where the different Brazilian regions can be observed, through an ethnomusicological view that seems to want to translate the folk essence of our people.
Keywords: Popular; Traditional; Ethnomusicology; Nationalism; Folk essence